New 1,3,4-thiadiazole compounds: synthesis, spectroscopic characterisation and theoretical analyses based on DFT calculations - Çavus, Muhammet Serdar; Muğlu, Halit (Balikesir Universitesi Fen Bilimleri Enstitusu Dergisi, 2018)
In this study, four novel 1,3,4-thiadiazole compounds, derived from α-methyl cinnamic acid, were synthesised. The structural elucidation was carried out using UV-Vis, FT-IR, 1H-NMR and 13C-NMR spectroscopy. In addition, the chemical and electronic properties of the compounds as well as UV-Vis, IR and NMR analyses were theoretically performed using the density functional theory (DFT). Based on the frontier molecular orbital (FMO) energies of the compounds, which were obtained from different methods and basis sets, some chemical reactivity parameters and their relationship with the methods were analysed. Theoretical calculations were compared with the experimental results. The electronegative substituents Cl and NO2 reduced the HOMO–LUMO energy gap (ΔE), and the ones caused a bathochromic shift in the UV absorption wavelength. The Pearson correlation coefficients between the experimental and theoretical IR and 13C NMR results were approximately R = 0.99. It was seen that, the chemical shift of hydrogen bound to an electronegative nitrogen atom was affected by intarmolecular hydrogen bond interactions.
Keywords: Engineering; Mühendislik; 3 4-tiadiazol; α-metil sinnamik asit; hesaplamalı kimya; yoğunluk fonksiyonel teorisi; 3 4-thiadiazoles; α-methyl cinnamic acid; computational chemistry; density functional theory; 3. Good health